2022
DOI: 10.1186/s13063-022-06747-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating a tool to improve engagement and recruitment of under-served groups in trials

Abstract: Background Despite substantial awareness that certain groups (e.g. ethnic minorities) are under-represented and under-served in trials, limited progress has been made in addressing this. As well as a public service and ethical duty to recruit and engage under-served groups in relevant research, importantly, there are clear scientific benefits, for example, increased generalisability. The key aims of the current study were to explore the following: general barriers and facilitato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…However, this is similar to the challenges when other equality tools were introduced, such as the Athena Swan Charter to improve gender equality and the INCLUDE Ethnicity Framework to improve inclusion of under-served groups in clinical research. Subsequent research has shown that the implementation of the Athena Swan Charter and the INCLUDE Ethnicity Framework has been associated with positive effects [ 50 52 ]. Therefore, we believe that the effects of the Framework are likely to be similar, provided each organisation commits to its implementation with sufficient resources and expertise.…”
Section: Discussionmentioning
confidence: 99%
“…However, this is similar to the challenges when other equality tools were introduced, such as the Athena Swan Charter to improve gender equality and the INCLUDE Ethnicity Framework to improve inclusion of under-served groups in clinical research. Subsequent research has shown that the implementation of the Athena Swan Charter and the INCLUDE Ethnicity Framework has been associated with positive effects [ 50 52 ]. Therefore, we believe that the effects of the Framework are likely to be similar, provided each organisation commits to its implementation with sufficient resources and expertise.…”
Section: Discussionmentioning
confidence: 99%
“…An implementation project was planned to identify and address any barriers to the uptake of the framework, some of which were identified during the pilot stage of the framework development and those identified by Trial Forge [ 22 , 24 ] during the implementation and evaluation if its ‘sister’ framework — the INCLUDE Ethnicity Framework. As a complex intervention that is intended to disrupt current systems for designing trials [ 30 ], we recognised the need for theorising how it would work in practice, which takes account of how it interacts with the context in which it is implemented [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…Working with researchers and people affected by capacity-affecting conditions and their carers, we developed the NIHR INCLUDE Impaired Capacity to Consent Framework to help researchers to design trials that are more inclusive of these groups [ 23 ]. Evidence from the development and evaluation of a previous INCLUDE framework — the Ethnicity Framework — showed that implementation activities are needed to help researchers to use a new framework in practice and are key for it to achieve similarly successful impact [ 24 ]. In this paper, we firstly outline the methods used in the development of the framework and the theoretically-informed implementation project that aims to support researchers to use the framework to design more inclusive trials in the future.…”
Section: Introductionmentioning
confidence: 99%
“…While the issues with the lack of diversity in research populations is well covered in the literature there are limited works on the views of research professionals around improving access to research. Two contemporary works, set in the UK, have been identified that explore researchers' views 30,32 . These works highlight general and specific barriers and facilitators to engagement, including lack of time and funding 32 and issues with approvals and consent processes 30 .…”
Section: Introductionmentioning
confidence: 99%
“…Two contemporary works, set in the UK, have been identified that explore researchers' views 30,32 . These works highlight general and specific barriers and facilitators to engagement, including lack of time and funding 32 and issues with approvals and consent processes 30 . They explore the complexity of engagement in these groups and the need for researchers to be proactive.…”
Section: Introductionmentioning
confidence: 99%